Spontaneous, independent, single-center renal denervation registry of a resistant hypertension multidisciplinary team. (3rd October 2022) - Fezzi, S; Castaldi, G; Widmann, M; Marin, F; Galli, V; Ruzzarin, A; Pesarini, G; Scarsini, R; Pighi, M; Tavella, D; Ribichini, F
Abstract: Background: Uncontrolled resistant hypertension (URH) is defined as PAS ≥140mmHg despite the adherence to at least 3 maximally tolerated doses of antihypertensive medications. In the adult population URH is a common condition with a prevalence that ranges between 10–15% and is related with poor prognosis and higher risk of major adverse cardiovascular events. Renal sympathetic denervation (RDN) has recently proved efficacy in different hypertensive subsets of patients. However, patients with chronic kidney disease (CKD) IIIB-V stages (i.e. glomerular filtrate rate <45 ml/min) have been systematically excluded from randomized clinical trials (RCT). Purpose: To evaluate the safety and the efficacy of RDN in a daily practice population of patients with URH on top of medical therapy, including patients with renal function impairment (GFR<45ml/min). Methods: Consecutive unselected patients with URH undergoing RDN were enrolled. Indication of RDN was assessed in a multidisciplinary team involving cardiologist, nephrologist and hypertension specialists, after secondary forms of hypertension had been excluded. Efficacy was defined as the inter-individual change of office (OBP) and ambulatory blood pressure monitoring (ABPM) at 3, 6 and 12 months after RDN. Safety as the absence of any device-related major complication (BARC classification), end-stage renal disease, stroke, acute myocardial infarction and any cause of death within 1 month of the procedure. Safety and efficacy profile was assessed in patients with an estimated GFR below 45 ml/min/1.73 m 2 . Results: Seventy-two patients underwent RDN for URH from 2012 to 2022. The population presented with multiple comorbidities and target organ damage: almost 50% were smoker, 43% diabetic, 33% PAD, 25% CAD and 60% CKD. Isolated systolic hypertension prevalence was 53%. The average number of antihypertensive medications at baseline was 5.3±1.1. Baseline OBP and ABPM were 158.8/86.6±23.4/15.3 mmHg and 151.4/87.6±18.8/14.2 mmHg, respectively. The vast majority of the procedures were performed with tetrapolar radio-frequency catheter (91.7%), with 37.3±14.3 number of ablations per procedure. The average amount of contrast medium was 72.1±38.1 ml. At 12-month follow-up a significant reduction of office and ambulatory systolic BP, respectively by −15.66±29.73 mmHg (P<0.01) and by −11.3±23.1mmHg (P<0.05), was noticed. BP reduction at 12-month follow-up among patients with eGFR <45 ml/min was similar to that obtained in patients with higher eGFR. No major complications were observed and renal function was stable up to 12 months, even in patients with lowest eGFR at baseline. Conclusion(s): RDN is safe and feasible in patients with URH on top of medical therapy, even in a high-risk CKD population with multiple comorbidities. Our experience underlines the central role of multidisciplinary team evaluation for the targeted management of uncontrolled resistant hypertension. Funding Acknowledgement: Type of funding sources: None.